New Model of Oropharyngeal Candidiasis in Mice - Kamai, Yasuki (American Society for Microbiology, 2001)
We established a straightforward murine model of oropharyngeal candidiasis. Mice were immunosuppressed with cortisone acetate, anesthetized, and then inoculated by placing cotton wool balls saturated with Candida albicans sublingually for 2 h. A prolonged, reproducible infection was induced. This model may be useful for antifungal screening or pathogenesis studies.